Persepsi Mahasiswa Nahdliyin terhadap Mata Kuliah Al Islam dan Kemuhammadiyahan di Perguruan Tinggi Muhammadiyah - Handoko, Puji; Akbar, Tian Khusni; Ya’qub, Muhammad; Rahajeng, Fitria; Setiyawan, Deni (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2024)
This research aims to explore the perceptions of Nahdlatul Ulama (NU) students regarding the Al-Islam and Kemuhammadiyahan (AIK) course at Muhammadiyah University of Gombong and to assess the effectiveness of the internalization of AIK values in the context of their daily lives. A survey was conducted among 100 NU students to understand their views on the comfort of studying at Muhammadiyah University, experiences of discrimination, and changes in perception towards Muhammadiyah before and after taking the AIK course. The method used was a qualitative approach with data collection techniques including in-depth interviews, participatory observation, and analysis of documents related to the Muhammadiyah course. The research results show that the majority of NU students feel comfortable studying at Muhammadiyah University of Gombong and do not experience discrimination. The AIK course is considered effective in introducing and deepening their understanding of Islamic teachings and the principles of Muhammadiyah, with 98.3% of students reporting a positive change in their views towards Muhammadiyah. Nevertheless, only 36.2% of students feel that the AIK material is relevant to their daily lives, indicating a need to better contextualize the learning material to make it more meaningful for NU students. Overall, this research concludes that Muhammadiyah University of Gombong has successfully integrated AIK values into the academic life of NU students, but there is a need to enhance the relevance of the material to the realities of student life to strengthen the internalization of these values.